VARIASI KOMPOSISI EKSTRAK BUNGA TELANG PADA PEMBUATAN SABUN MANDI SEBAGAI PEWARNA ALAMI - Desti Lidya; Sofiah Sofiah; Meilianti Meilianti; Azizil Tasya Bighoiri (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
A chemical product in the form of soap, namely by mixing triglycerides with potassium hydroxide (KOH) using a method called the saponification method. In this study, the product added variations in the composition of olive oil and butterfly pea extract. variations in the composition of olive oil with three variations, namely 15 ml, 30 ml, and 45 ml. The butterfly pea flower extract was then used in three different concentrations: 2 ml, 4 ml, and 6 ml. This composition variation is divided into nine samples with the addition of olive oil and butterfly pea flower extract, respectively. The resulting product has been tested in four categories: pH test, free fatty acid test, ethanol insoluble substance test, and active ingredient test. The experimental results that met SNI 2588-2017 were sample 1, with a variation of the composition of 15 ml of olive oil and 2 ml of butterfly pea flower extract. with a pH test result of 5, an insoluble test result in ethanol of 0.16%, a free fatty acid test result of 0.2256%, an active ingredient test result of 24%, and an organoleptic test result in three categories, namely color, odor, and shape, is level 4 (preferred).